Strategies to maintain nutrient intake, reduce weight loss, and improve livability in newly weaned pigs - Wensley, Madison Renae (Kansas State University, 2022)
Low feed consumption after weaning disrupts nutrient intake and results in what is commonly known as a post-weaning growth check. While most pigs recover from this initial reduction in feed intake, some pigs fail to successfully transition after weaning, leading to decreased survivability. As nursery pig mortality continues to increase across the swine industry, there is need to optimize current intervention and management practices. Hence, two literature reviews were written to summarize several pre- and post-weaning strategies that can be used to improve feed intake after weaning. Increasing weaning age helps prevent many of the adverse effects associated with weaning stress. Other pre-weaning strategies include creep feeding and piglet socialization. These strategies familiarize pigs with solid feed, encourage exploratory behavior, and improve social skills prior to weaning. Post-weaning strategies include appropriate barn temperatures, nutrient resource availability, and placement strategies. Because young pigs are sensitive to palatability, diet form and complexity are also important considerations. To evaluate the gaps in knowledge identified from these literature reviews, 10 experiments were conducted using 16,183 pigs. The first series of experiments evaluated the effect of mat feeding on the growth performance, removal, and mortality of nursery pigs. A second series of experiments evaluated different sensory attractants offered pre- and post-weaning on the feed intake and body weight loss of nursery pigs after weaning. The effect of gruel feeding and supplemental oral dextrose on nursery pig survivability was also assessed. Lastly, a single experiment evaluated the effect of Duroc sire lines selected for either early or late maturing growth rates and creep feeding on the stress response, intestinal permeability, and growth performance of nursery and finishing pigs. Implementation of these strategies had limited effects on nursery pig growth performance; however, they did show we can successfully reduce the percentage of pigs that lose weight after weaning. Likewise, mat feeding can be used to reduce the removal rate of pigs in the nursery. In contrast, gruel feeding four times per day vs two times per day or providing a dextrose supplement to pigs removed from the general population did not improve survivability. Nutritional attempts to maintain feed intake have minimal effects compared to genetic selection. Early maturing pigs had a lower stress response at weaning and improved ADG and ADFI until approximately 100 kg, at which point late maturing pigs began to exhibit higher ADG. Late maturing pigs had improved feed efficiency throughout the experiment. Additionally, creep feeding late maturing pigs resulted in improved growth performance compared to providing no creep feed, whereas creep feed did not impact early maturing pigs. In summary, innately low feed intake after weaning makes it difficult to influence nursery pig growth performance. However, these data indicate that feeding and management strategies can be used to successfully reduce the percentage of pigs that lose weight after weaning, as well as removal and mortality rates. These strategies also increase animal caretaker engagement in the barn. As important as feeding and management strategies, the health and genetics of pigs plays a crucial role in how pigs transition at weaning.
Keywords: Mat feeding; Sensory attractant; Sire line; Gruel feeding; Wean pig; Survivability